THE CONCEPT AND THE EXPERIENCE IN DESIGNING THE STRATEGY FOR INNOVATIVE DEVELOPMENT OF UNIVERSITY - Evgeny V. Chuprunov; Roman G. Strongin; Alexandr O. Grudzinsky (Высшее образование в России)
The article presents the concept of the development of an innovative university strategy. It is illustrated by the example of the strategy adopted by Lobachevsky State University of Nizhni Novgorod – National Research University. The experience in collective discussion and adoption of the strategy in a large multidisciplinary classical university is analyzed. The adopted strategy became a fundamental part of UNN successful application for the Leading University International Competitiveness Enhancement Program.